Sistema de avaliação de capacidade dinâmica do membro inferior - Schneider, Paulo Sérgio (2020)
The present work presents a proposal of a biomedical equipment capable of expose subjects to movements similar to car braking and acquiring information such as the response time and the effort made by lower limbs of patients. Especially after rehabilitation of knee injuries, the evaluation of these parameters can be used to monitor their recovery. This research project aims to collaborate with the formation of a protocol that identifies whether the patient is able to safely drive and brake or even be released for sport activities after treatment of injuries to the right knee. The choice of braking movement is given because it is an activity that can prevent accidents where, in addition to new injuries to the driver, other people could be victimized. An equipment similar to a car cockpit has been developed. It has been equipped with sensors to detect some movement characteristics and visual indicators, used to stimulate the user to perform a simulated emergency braking. The mechanical effort made by the user is applied to a pedal, coupled to a mechanical system and connected to a load cell. The electrical signal is then amplified and acquired by a microcontrolled system. From the acquired data, time force diagrams can be presented. Satisfactory results compatible with those generated in real braking have been obtained, indicating the possibility of using the proposed system to check the braking effort.